The influence of plasticity-induced crack closure on creep-fatigue crack growth in two heat-resistant steels. (August 2019) - Ramirez, J.; Potirniche, G.P.; Shaber, N.; Taylor, M.; Pugesek, H.; Stephens, R.; Charit, I.
Highlights: Load hold time decreases the crack-tip opening load in creep-fatigue crack growth. Load hold time increases crack growth rates during subsequent cyclic load steps. Creep loading influence on plasticity-induced crack closure reveals load interaction effects. Finite element method can be used to predict creep-fatigue crack growth in high temperature steels. Abstract: Finite element simulations are performed to predict plasticity-induced crack closure and creep-fatigue crack growth rates in two heat-resistant steels, the austenitic 20Cr-25Ni (Alloy 709) and martensitic 9Cr-1Mo (modified 1Cr-9Mo) steels. In a creep-fatigue cycle, total crack growth rate is usually computed by the addition of the fatigue crack growth rate during cyclic loading and creep crack growth rate during hold time. Two-dimensional finite element analyses of compact tension specimens are performed to simulate crack growth under cyclic and time-dependent loading conditions, with the consideration of elastic-plastic and creep deformations of the material at the crack tip. The simulations quantify the effect of hold time on crack opening load induced by the combined action of plasticity-induced crack closure and creep-induced stress relaxation at the crack tip. It is shown that increasing hold time during a creep-fatigue cycle results in a decrease of crack-tip opening load, thus increasing crack growth rate during the next cyclic loading. Experimental results of creep-fatigue crack growth rates in Alloy 709 are presented. The finite element simulations predicted crack growth rates under creep-fatigue loading in agreement with experimental values for both Alloy 709 and modified 9Cr-1Mo steels.